Characterization of wind-induced pressure on membrane roofs based on full-scale wind tunnel testing. (15th May 2021) - Estephan, Johnny; Feng, Changda; Gan Chowdhury, Arindam; Chavez, Mauricio; Baskaran, Appupillai; Moravej, Mohammadtaghi
Highlights: Membrane roofs account for over 60% of low-sloped building roofs in North America. The effect of roof flexibility is not accounted for in building design codes. Full-scale wind-tunnel testing was conducted on two flexible roof systems and plywood roof. The lowest pressures were observed on the most flexible roof system due to membrane deformation. Abstract: Flexible roofing systems (e.g., membrane roofs) are widely used in low-rise commercial and industrial buildings, accounting for over 60% of low-sloped building roofs in North America. Despite their wide usage, the effects of roof flexibility are neither thoroughly studied, nor accounted for in current building design codes and standards. To investigate such roof flexibility effects on wind-induced pressure, full-scale testing was conducted at the NHERI Wall of Wind (WOW) Experimental Facility (EF). The mechanically attached roof system (MARS) and partially adhered roof system (PARS), two of the most commonly used commercial roofing systems with different flexibility characteristics, were considered in this study. "U-shaped" pressure taps were used to measure the wind-induced pressure on the membrane roof, and the pressure coefficients were compared to those measured on a plywood roof. The effects of wind direction and wind speed on the wind-induced pressure coefficients of membrane roofs were studied. The results showed that the membrane deformation due to the membrane roof flexibility resulted in a reduction in the peak pressure coefficients as compared to those of rigid plywood roof. This reduction in wind loads is more significant for the MARS (27%) which has more flexibility than the PARS (19%). The membrane roof flexibility also modifies the non-Gaussian characteristic which results in a lower peak factor than the plywood roof. It was also observed that peak pressure coefficients on the flexible roof increase at higher wind speeds. This study provides an improved understanding of the effect of roof flexibility on wind-induced pressure coefficients. Further research is needed by testing more types and configurations of flexible roofs to formulate new code provisions for wind effects on flexible membrane roofs.